The Role of Women in Politics in Indonesia: Critical Review of Islamic Law - Aslati, Aslati; Rahman, Rahman; Silawati, Silawati; Hardani, Sofia; Albahi, Muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
The role of women in politics in Indonesia continues to be a relevant topic in social and religious discourse. Although women's participation in politics has increased since the reform era, their representation is still far from the ideal proportions. This phenomenon raises various questions about the obstacles faced by women, especially in the context of a strong patriarchal culture and religious interpretations that often limit women's space for movement. This study aims to analyze the role of women in Indonesian politics through a critical review of Islamic Law. This study uses a qualitative method with a descriptive-analytical approach. Data were collected through literature studies involving classical and contemporary Islamic literature, relevant laws, and empirical data related to women's participation in Indonesian politics. The results of the study show that normatively, Islam provides space for women to contribute in the public sphere, including politics, by emphasizing the principles of justice and equality. However, its implementation in the Indonesian context is still influenced by conservative religious interpretations and unsupportive social structures. In addition, factors such as lack of access to political education, gender stigma, and lack of institutional support also reinforce these barriers. This study recommends a more inclusive reinterpretation of religious texts and the strengthening of affirmative policies to increase the role of women in politics. With this effort, it is hoped that a fairer and more participatory political ecosystem will be created, in line with Islamic and democratic values.